Anti-wear properties evaluation of frictional sliding interfaces in automobile engines lubricated by copper/graphene nanolubricants - Mohamed Kamal Ahmed Ali; Xianjun Hou; Mohamed A. A. Abdelkareem (Friction)
Abstract Owing to the significance of improving fuel economy, reducing emissions, and extending the durability of engine components, this study focused on the tribological performance of nano-additives. In this study, copper (Cu) and graphene (Gr) nanomaterials were dispersed in a fully formulated engine oil (5W-30) with different concentrations. The tribological trials were investigated under various speeds and loads, utilizing a reciprocating tribometer to mimic the ring/liner interfaces in the engine. The frictional surface morphologies were comprehensively analyzed using electron probe X-ray microanalysis (EPMA), field emission scanning electron microscopy (FESEM), energy dispersive spectrometer (EDS), and three dimensional (3D) surface profilometry to explore the mechanisms responsible for improving the tribological performance of the frictional sliding parts in the engine. The tribological test results illustrated that lubrication by nano-additives reduced the wear rate (WR) and friction coefficient (COF) by 25%–30% and 26.5%–32.6%, respectively, as compared with 5W-30. The results showed that this is a promising approach for increasing the durability and lifespan of frictional sliding components and fuel economy in automobile engines.